Enhancing the initial acceleration performance of elite rugby backs. Part I: Determining individual technical needs - Wild, J. J.; Bezodis, I. N.; North, J. S.; Bezodis, N. E. (International Journal of Sports Physiology and Performance, 2023)
Purpose: This study sought to quantify the within-individual relationships between spatiotemporal variables and initial acceleration sprint performance in elite rugby backs and to establish a normative data set of relevant strength-based measures.